ANALISIS EKONOMI SYARIAH TERHADAP PENGGUNAAN STRATEGI DALAM PENINGKATAN MINAT FILANTROPI MASYARAKAT (STUDI LAZISMU KOTA PAREPARE) (Jurnal Ekonomi Bisnis dan Akuntansi, 2022)
This study aims to determine the strategy of LAZISMU City of Parepare in managing Zakat, Infak and Alms, to find out the increase in community philanthropic interest in zakat, infaq and alms and to find out how Islamic economic analysis is done in LAZISMU City of Parepare in managing Zakat, Infak and Alms. The type of research used in this study is descriptive qualitative, namely digging up information in depth by conducting direct interviews to the field. While the instrument method approach is to use strategic management approach instruments, philanthropic theory and sharia management. The place of this research is LAZISMU Parepare City. The results of this study indicate that LAZISMU's strategy in managing zakat, infaq and alms consists of a planning strategy, promotion strategy, collection strategy, distribution strategy and evaluation strategy. The increase in philanthropic interest in the people of Parepare City from 2017 to 2019 has continuously increased the number of donors, whereas in 2020 it is different from the previous year, the situation with the covid-19 pandemic greatly affected the increase in philanthropic interest in the people of Parepare City resulting in a decrease in the number of donors due to the lockdown situation which reduces community activity. LAZISMU in managing zakat, infaq and alms is applied based on sharia management and contains strategies for sharia economic principles as taught by Rasulullah saw. which includes justice, trust and accountability, and communicative. In addition, the Prophet Muhammad taught the qualities of honesty (sidq) and intelligence (fathanah).